The effects of effluent water irrigation and salinity on soil chemical properties and three species of perennial grass - Isweiri, Hanan F., author; Qain, Yaling, advisor; Barbarick, Ken, committee member; Davis, Jessica, committee member; Hughes, Harrison, committee member; Koski, Anthony, committee member (Colorado State University. Libraries, 2017)
To view the abstract, please see the full text of the document.